Transportation Modeling as a Didactic Tool: Human Settlement and Transport. (October 2015) - Ohnmacht, Timo; von Arx, Widar; Schick, Norbert; Wegelin, Philipp; Frölicher, Jonas
Background .Interconnections of settlement, transportation, and society are extremely varied, complex, and context-specific. The Simulation Game HUMAN SETTLEMENT AND TRANSPORT (HST) aims to assist in the training and continuing education of transportation students and professionals with thetransportation modeling software VISUM. Aim . The key research questions are as follows: Cantransportation models be used as didactic tools to improve the teaching on causal chains between land use and transport? Why and how does transport modelingenhance students learning in transportation planning and settlement structure ? What are theself-reported learning outcomes and how do they vary from conventional didactic settings such as chalk-and-talk teaching, case studies, closed exercises, and desk research? Method . A case study is used toevaluate the game's ability to simulate the complexity of actual human settlement and transportation. We focus onself-reported learning and how the expert game encourages students to discover knowledge. Results . Thisexpert game successfully replicated complex and context-specific scenarios that actualurban planning committees might face. Participants revealed that theyunearthed interrelations between settlement, transportation, and society similar to those found in the relevant academic literature. Conclusions . The results affirm the game's effectiveness as an educational tool fortransportation engineering, urban planning, andtransportation modeling students and professionals. Recommendation . This research suggests that properly incorporating policy games into the curriculum can enhance students' learning in transportation planning and settlement structure.